The Use of Instagram as A Media for Learning Simple Present Tense of The Eighth-Grade Students of SMP N 3 Palembang in The 4.0 Era - Wulandari Octaviani; Nike Angraini; Badriyah Ulfah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
In the pandemic era, all learning processes are transferred online using digital learning media. Learning media can be easily found by utilizing the digital era 4.0, one of which is the use of social media Instagram as a learning medium for teachers and students who can motivate and entertain students while studying. This research identified two problems: the significant improvement of the eighth-grade students at SMP N 3 Palembang and the significant mean difference between students who learned simple present tense by using social media Instagram as a medium for learning and who were not. This research was the quantitative method. The sample in this study was selected by purposive sampling method. The experimental and control groups were given a pre-test and a post-test to collect data. The findings of this research revealed that there was a significant improvement for the experimental class of 19.33 while for the control was only 3.57. It can be said that the research results from these two groups are the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. As a result, in the digital era, teachers can use Instagram as one of the learning media for students.